Maintenance therapies in metastatic pancreatic cancer: present and future with a focus on PARP inhibitors. (July 2020) - Hammel, Pascal; Vitellius, Carole; Boisteau, Émeric; Wisniewski, Mathilde; Colle, Elise; Hilmi, Marc; Dengremont, Christelle; Granier, Sandra; Turpin, Anthony; de Mestier, Louis; Neuzillet, Cindy
Metastatic pancreatic ductal adenocarcinomas (PDACs) are now more effectively controlled using chemotherapy combinations such as FOLFIRINOX and gemcitabine plus nab-paclitaxel (NabP) regimens with a subset of patients who achieve a sustained tumor stabilization or response. The next challenge is to design maintenance therapies that result in continued tumor control with minimal toxicity. Quality of life should always be a priority in these patients with prolonged survival. Gradually tapering off the intensity of chemotherapy by suppressing drug(s) in the combination is one option. Thus, maintenance with 5-fluorouracil or gemcitabine as single agents after FOLFIRINOX or gemcitabine-NabP induction, respectively, seems to be a promising approach to minimize neurotoxicity while maintaining efficacy. Another option is to introduce maintenance drug(s) with different anti-tumoral actions. The recent example of olaparib in patients with BRCA mutated PDAC provides a promising proof-of-concept of a switch maintenance strategy in this setting.